THE INFLUENCE OF ATTITUDES, SUBJECTIVE NORMS AND BEHAVIORAL CONTROLS ON ENTREPRENEURIAL INTENTIONS OF ELEMENTARY SCHOOL TEACHER EDUCATION STUDENTS, JAKARTA STATE UNIVERSITY - Zillah, Isfanz Ainu; Eryanto, Henry; Usman, Osly (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2021)
The purpose of this study was to determine the effect of attitudes, subjective norms and behavioral control on entrepreneurial intentions in Primary School Teacher Education students, Faculty of Education, UNJ 2017. The research method used was a survey method with a descriptive approach, the population used was all teacher education students. Elementary School, Faculty of Education UNJ. The model in this study uses a path analysis model. The analytical technique used in this study uses SEM (Structural Equation Modeling) which is operated with the SmartPLS version 3.0 program for hypothesis testing. The analysis technique carried out in PLS includes three stages, namely external model analysis, internal model analysis, and hypothesis testing. The results obtained are attitudes have a positive and significant effect on entrepreneurial intentions, subjective norms have a positive and significant effect on entrepreneurial intentions, behavioral control has a positive and significant effect on entrepreneurial intentions, and attitudes, subjective norms and behavioral controls have a positive and significant effect on entrepreneurial intentions.